2000
DOI: 10.1046/j.1444-2906.2000.00044.x
|View full text |Cite
|
Sign up to set email alerts
|

Productivity of a Sargassum macrocarpum (Fucales, Phaeophyta) population in Fukawa Bay, Sea of Japan

Abstract: SUMMARY: The productive structure and productivity of a Sargassum macrocarpum C. Agardh population were studied from June 1993 to July 1994 in Fukawa Bay facing the Sea of Japan, Yamaguchi Prefecture. S. macrocarpum formed a dense population at a depth of 8 m in the study area. Using the stratified clip technique, monthly changes in the productive structure from 1993 to 1994 were clarified. The dry weight of leaves and main branches increased with the elongation of branches. Thalli in the middle to high stratu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 13 publications
0
39
2
Order By: Relevance
“…As the seasonal population development of S. fusiforme in our study was similar to the populations in the Pacific region, the recruits we observed were considered to be ramets and they mainly contributed to maintain the population as the previous studies have indicated (Suto 1951; Arai and Arai 1983). Biomass allocation of receptacles relative to the total biomass at the seasonal peak of maturation was lower in S. fusiforme in this study (14 %) than those in other Sargassum species reported so far, e.g., 20–24 % in Sargassum muticum (Yendo) Fensholt (Arenas and Fernández 1998) and 34 % in Sargassum macrocarpum C. Agardh (Murase et al 2000), also indicating the relative importance of vegetative reproduction in S. fusiforme .…”
Section: Discussioncontrasting
confidence: 59%
“…As the seasonal population development of S. fusiforme in our study was similar to the populations in the Pacific region, the recruits we observed were considered to be ramets and they mainly contributed to maintain the population as the previous studies have indicated (Suto 1951; Arai and Arai 1983). Biomass allocation of receptacles relative to the total biomass at the seasonal peak of maturation was lower in S. fusiforme in this study (14 %) than those in other Sargassum species reported so far, e.g., 20–24 % in Sargassum muticum (Yendo) Fensholt (Arenas and Fernández 1998) and 34 % in Sargassum macrocarpum C. Agardh (Murase et al 2000), also indicating the relative importance of vegetative reproduction in S. fusiforme .…”
Section: Discussioncontrasting
confidence: 59%
“…All these studies reported highest biomass for Sargassum during cool periods. Conversely, Murase et al (2000) reported the highest S. macrocarpum productivity during summer in Japan, and Kilar and Norris (1988) did not detect any clear seasonal pattern in S. filipendula from Caribbean Panama.…”
Section: Spatial and Seasonal Variationmentioning
confidence: 51%
“…O. Kuntze is a common species in the rocky intertidal zone along the western North Pacific (Phillips 1995). This alga plays important ecological roles in the coastal ecosystem due to the large biomass and high productivity (Murae et al 2000). Because of its potentials in alginate production and bioactive extraction, S. thunbergii is also of great economic importance.…”
Section: Introductionmentioning
confidence: 99%